Education Reform and Quality Training of Music Majors From the Perspective of Entrepreneurial Education - Jiang, Yue (Frontiers in Psychology, 2021)
Art major graduates are facing more severe employment pressure. Based on entrepreneurial education, the reform of entrepreneurship education and quality training of music majors in colleges and universities are analyzed. First, the relevant theories of entrepreneurship education are introduced and the advantages of advanced entrepreneurship education in foreign countries are analyzed. Second, the music majors in a university are selected as the subjects to analyze the current situation of entrepreneurship of music majors. Finally, new strategies are put forward for the reform of entrepreneurship education of music majors. The research shows that the number of music majors who are very interested in entrepreneurship accounts for 22.2%. In terms of the music majors' understanding of entrepreneurship policies, the proportion of students with less understanding accounts for 40.1%. As for the ways of music majors to acquire entrepreneurship knowledge, 8.00% usually turn to books and networks. Music majors hope to get support from the government and schools in the cultivation of entrepreneurship. In entrepreneurship, music majors who intend to start a business according to their interests account for 40.8%. The variance of eigenvalues of the four main factors is 19.49%, 12.96%, 10.75%, and 8.39% respectively, and their contribution value is 51.58%. The four research aspects of entrepreneurship education are music majors' entrepreneurship policy, entrepreneurship desire, and entrepreneurship quality and entrepreneurship education practice. The entrepreneurship education system is to arouse interest, improve entrepreneurial ability, and form entrepreneurial personality. This paper proposes good entrepreneurship education strategies.